Foam aerated biofilm reactor: a novel counter-diffusional process for COD and nitrogen removal from low COD/N effluents. Issue 17 (29th July 2022) - Silva, Bruno Garcia; Santos Oliveira, Jean Maikon; Zamariolli Damianovic, Márcia Helena Rissato; Foresti, Eugenio
ABSTRACT: Counter-diffusional biofilms are efficient in the removal of nitrogen from low strength wastewaters. Although counter-diffusion is usually established using expensive gas-permeable membranes, a polyurethane sheet is used to separate the aerobic and anoxic environments in the novel foam aerated biofilm reactor (FABR). Foam sheets with thicknesses of 10, 5 and 2 mm and synthetic wastewater with COD/N ratios of 5 and 2.5 were evaluated. The 2 mm thick foam reactor did not show good biomass adherence and, therefore, did not show N removal efficiency. The 5 and 10 mm reactors, in both COD/N ratios, showed similar total nitrogen and COD removal performance, up to 60% and 80%, respectively. The denitrification efficiency was close to 100% throughout the experimental period. Nitrification efficiency decreased with microbial growth, which was recovered after removal of excessive biomass. Lower values of polyurethane foam thickness and COD/N ratio did not provide a higher nitrification rate, as expected. The increase in resistance to mass transfer was associated with the growth of biomass attached to the foam rather than to its thickness and resulted in specialization of the microbial communities as revealed by 16S amplicon sequencing. FABR reveals as a promising alternative for simultaneous removal of nitrogen and COD from low COD/N ratio wastewaters. GRAPHICAL ABSTRACT: UF0001